2010
DOI: 10.1016/j.ssc.2009.12.008
|View full text |Cite
|
Sign up to set email alerts
|

Heat and spin transport in magnetic nanowires

Abstract: a b s t r a c tTransport measurements are carried out in which temperature oscillation is applied to magnetic nanostructures. Using spin valves, this measurement reveals aspects of the spin transport in non-collinear configurations. In one implementation, an AC voltage is detected when a DC current is driven through the nanostructure under test and its temperature is made to oscillate by illuminating it with a laser diode. A simpler approach is presented that relies on Joule heating to generate the temperature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…27 They predicted that in a tunnel junction with at least one of metallic electrodes being ferromagnetic, magnetization currents could be induced both electrically and thermally, and vice versa, thermal and electrical currents could also be induced magnetically. Later, similar concepts were considered theoretically in a variety of nanosys-tems, including magnetic tunnel junctions, [28][29][30][31] spin valves, [32][33][34] quantum dots, [35][36][37][38][39][40] , single-molecule-magnet junctions, 41,42 and multilayered systems. 43,44 In the present paper we focus on a certain aspect of spin-related thermoelectric effects in nanoscopic systems that has not drawn much attention so far, namely on the influence of magnetic anisotropy of a system on its thermoelectric properties.…”
Section: Introductionmentioning
confidence: 99%
“…27 They predicted that in a tunnel junction with at least one of metallic electrodes being ferromagnetic, magnetization currents could be induced both electrically and thermally, and vice versa, thermal and electrical currents could also be induced magnetically. Later, similar concepts were considered theoretically in a variety of nanosys-tems, including magnetic tunnel junctions, [28][29][30][31] spin valves, [32][33][34] quantum dots, [35][36][37][38][39][40] , single-molecule-magnet junctions, 41,42 and multilayered systems. 43,44 In the present paper we focus on a certain aspect of spin-related thermoelectric effects in nanoscopic systems that has not drawn much attention so far, namely on the influence of magnetic anisotropy of a system on its thermoelectric properties.…”
Section: Introductionmentioning
confidence: 99%
“…Early studies [35,46,47] showed that magnetothermoelectric power data for F/N multilayers in the CPP geometry behaved similarly to CPP-MR data, with modestly larger fractional changes with H. Data on more complex phenomena, such as a spin-dependent Peltier effect [35], including when both heat and charge currents are flowing [35], as well as effects involving noncollinear spin orientations [130], have been reported. Figure 20 [35] compares CPP-MR, CPP-magnetothermopower (MTP), and an ac CPP magneto-thermalgalvanic voltage (MTGV) signal detected with both an ac applied temperature difference and a constant 200 mA current through the sample.…”
Section: Magnetothermoelectricity and Thermal Conductancementioning
confidence: 96%
“…We also find that the baseline of the 𝑉 2𝑓 response can be strongly affected by an applied dc current. [11] The peak height of 𝑉 2𝑓 can reach up to 1000% relative to the baseline in some samples (Fig. 2).…”
mentioning
confidence: 94%